Goal-Directed Intraoperative Fluid Therapy Benefits Patients Undergoing Major Gynecologic Oncology Surgery: A Controlled Before-and-After Study - Yu, Jiawen; Che, Lu; Zhu, Afang; Xu, Li; Huang, Yuguang (Frontiers in Oncology, 2022)
Background: Fluid management during major gynecologic oncology surgeries faces great challenges due to the distinctive characteristics of patients with gynecologic malignancies as well as traits of the surgical procedure. Intraoperative goal-directed fluid therapy (GDFT) has been proved to be effective reducing postoperative complications among major colorectal surgeries, however, the efficacy of GDFT has not been fully studied in gynecologic malignancy surgeries. This study aimed to discuss the influence of GDFT practice in patients undergoing major gynecologic oncology surgeries. Methods: This study was a controlled before-and-after study. From June 2015 to June 2018 in Peking Union Medical College Hospital, a total of 300 patients scheduled for elective laparotomy of gynecological malignancies were enrolled and chronologically allocated into two groups, with the earlier 150 patients in control group and the latter 150 patients in GDFT group. The GDFT protocol was applied by Vigileo/Flotrac monitoring of stroke volume and fluid responsiveness to guide intraoperative fluid infusion and use of vasoactive agents. The primary outcome was postoperative complications within 30 days after surgery. The secondary outcome included length of stay and time of functional recovery. Results: A total of 249 patients undergoing major gynecologic oncology surgeries were analyzed in the study, with 129 in the control group and 120 patients in the GDFT group. Patients in GDFT group had higher ASA classifications and more baseline comorbidities. GDFT patients received significantly less fluid infusion than control group (15.8ml/kg/h vs 17.9ml/kg/h) while fluid loss was similar (6.9ml/kg/h vs 7.1ml/kg/h). GDFT was associated with decreased risk of postoperative complications (OR 0.572, 95%CI 0.343 to 0.953, P 0.032), especially surgical site infections (OR 0.127, 95% CI 0.003 to 0.971, P 0.037). The postoperative bowel function recovery and length of hospital stay were not significantly different between two groups. Conclusion: Goal-directed intraoperative fluid therapy is associated with less postoperative complications in patients undergoing major gynecologic oncology surgeries.